2009
DOI: 10.1158/1078-0432.ccr-08-2660
|View full text |Cite
|
Sign up to set email alerts
|

Starving the Addiction: New Opportunities for Durable Suppression of AR Signaling in Prostate Cancer

Abstract: Clinical data and models of human disease indicate that androgen receptor (AR) activity is essential for prostate cancer development, growth, and progression. The dependence of prostatic adenocarcinoma on AR signaling at all stages of disease has thereby been exploited in the treatment of disseminated tumors, for which ablation of AR function is the goal of first-line therapy. Although these strategies are initially effective, recurrent tumors arise with restored AR activity, and no durable treatment has yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
280
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(281 citation statements)
references
References 65 publications
(68 reference statements)
0
280
0
1
Order By: Relevance
“…Based on the central role of AR in castration resistance, novel AR pathway inhibitors could potentially provide important therapeutics for advanced prostate cancer (Attar et al 2009;Knudsen and Scher 2009). In this regard, a second-generation AR antagonist, MDV3100, which completely lacks agonist activity and binds AR with greater affinity than bicalutamide, has provided new insights into castration resistance, and has given promising results in mouse models and in a human phase 1-2 trial Scher et al 2010).…”
Section: Manipulating Ar Signaling For Prevention and Treatmentmentioning
confidence: 99%
“…Based on the central role of AR in castration resistance, novel AR pathway inhibitors could potentially provide important therapeutics for advanced prostate cancer (Attar et al 2009;Knudsen and Scher 2009). In this regard, a second-generation AR antagonist, MDV3100, which completely lacks agonist activity and binds AR with greater affinity than bicalutamide, has provided new insights into castration resistance, and has given promising results in mouse models and in a human phase 1-2 trial Scher et al 2010).…”
Section: Manipulating Ar Signaling For Prevention and Treatmentmentioning
confidence: 99%
“…Androgens mediate their actions through binding to the androgen receptor (AR), a ligand-dependent transcription factor and a member of the nuclear receptor superfamily. A plethora of adaptive mechanisms including AR amplification, mutation, and expression of splice variants has been demonstrated to maintain functional receptor signaling in CRPC (Scher et al 2004, Knudsen & Scher 2009, Mills 2014, and consequently AR remains the primary therapeutic target for metastatic and advanced prostate cancer (Knudsen & Scher 2009). The development and FDA approval of agents that more effectively target AR signaling, including enzalutamide (Xtandi; an AR antagonist) and abiraterone acetate (Zytiga; an inhibitor of intratumoral androgen synthesis) (Tran et al 2009, Cai & Balk 2011, Rodrigues et al 2014, has expanded the therapeutic options for CRPC.…”
Section: Androgens and Prostate Cancermentioning
confidence: 99%
“…Chen et al 3 , using transcript profiling of human prostate cancer xenografts, elegantly demonstrated that an increase in AR expression was consistently associated with the development of CRPC and that the increased level of AR was both necessary and sufficient to convert prostate cancer growth from hormone-sensitive to hormone-refractory. Importantly, functional AR signalling appears to be inappropriately restored in the castrate or androgen-deplete environment, including AR amplification and/or overexpression, gain-of-function AR mutations that facilitate ligand promiscuity or spliced variants that are constitutively active, intracrine androgen production, overexpression of AR coactivators, and indirect AR activation by growth factors, cytokines or aberrant AR phosphorylation 2,[4][5][6][7] . These AR-dependent mechanisms highlight that a common feature of CRPC is an addiction to AR signalling 5 .…”
mentioning
confidence: 99%
“…Importantly, functional AR signalling appears to be inappropriately restored in the castrate or androgen-deplete environment, including AR amplification and/or overexpression, gain-of-function AR mutations that facilitate ligand promiscuity or spliced variants that are constitutively active, intracrine androgen production, overexpression of AR coactivators, and indirect AR activation by growth factors, cytokines or aberrant AR phosphorylation 2,[4][5][6][7] . These AR-dependent mechanisms highlight that a common feature of CRPC is an addiction to AR signalling 5 . Therefore, there remains a critical and unmet need for novel therapeutic agents that can directly target and inhibit the AR in advanced prostate cancer by means other than inhibiting androgen-induced activation.…”
mentioning
confidence: 99%